Collective Action and Social Relations: The Limits of Olson’s Theory and the Primacy of Social Capital in Community Empowerment Programs in Riau, Indonesia - Faridl Widhagdha, Miftah; Muktiyo, Widodo; Kartono, Drajat Tri; Padmaningrum, Dwiningtyas (Indonesian Journal of Social Responsibility Review (IJSRR), 2026)
The success of community empowerment programs, particularly CSR, heavily relies on the collective action of local groups. Mancur Olson's (1971) theory of collective action prioritizes small, homogeneous, and focused groups, but it often fails to explain sociological realities in the field, especially in Indonesia. This article critiques Olson using qualitative data from three CSR beneficiary groups of an Oil Refinery Company in Bengkalis, Riau Province, Indonesia. Although the Tunas Makmur Farmers Group and the Harapan Bersama Fishermen Group support Olson's theory, the case of the formal, heterogeneous Masyarakat Peduli Api (MPA) group challenges this logic, as its effectiveness is not correlated with size. The main argument is that Olson's model is incomplete. The success of collective action is determined by sociological prerequisites: social relations or social capital (norms, trust, networks). Homogeneity is merely a proxy for strong social relations. Therefore, Collective Action Theory must be modified by integrating social relations as the determining foundation for the functioning of Olson's determinants